P436 SPOSAB ABP 501 - A Sicilian Prospective Observational Study of Patients with Inflammatory Bowel Disease Treated with Adalimumab Biosimilar ABP 501. (27th May 2021) - Macaluso, F; Cappello, M; Busacca, A; Fries, W; Viola, A; Costantino, G; Magnano, A; Vinci, E; Ferracane, C; Privitera, A C; Piccillo, G; Belluardo, N; et al.
Abstract: Background: Clinical data on the use of Adalimumab (ADA) biosimilar ABP 501 in inflammatory bowel disease (IBD) are lacking. Methods: SPOSAB ABP 501 is a multicenter, observational, prospective study performed among the cohort of the Sicilian Network for Inflammatory Bowel Disease (SN-IBD). All consecutive patients with Crohn's Disease (CD) or Ulcerative Colitis (UC) treated with ABP 501 from the introduction of the drug in Sicily (February 2019) to February 2020 (12 months) were enrolled. Patients were divided into 3 groups (group A: naive to ADA and naive to anti-TNFs; group B: naive to ADA and previously exposed to anti-TNFs; group C: switch from ADA originator to ABP 501). The primary end-point was the assessment of safety, in terms of rate of serious adverse events (SAEs). Secondary end-point was the evaluation of effectiveness, in terms of clinical response and steroid-free clinical remission at 12 weeks for group A and B, and as treatment persistency for all 3 groups. Results: 559 patients (median age 39 years; CD 88.0%, UC 12.0%) were included [group A: 189 (33.8%); group B: 30 (5.4%); group C: 340 (60.8]. Overall, the mean follow-up was 8.7 months (median 10.0 months, interquartile range: 6.0–12.0 months), and the total follow-up time was 403.4 patient-years. 36 SAEs occurred in 36 patients (6.4%), with an incidence rate of 8.9 per 100 person-years (PY), and 22 of them caused the withdrawal of the drug (incidence rate: 5.5 per 100 PY). The incidence rate of SAEs was higher among patients in group A compared with group C (17.4 vs. 4.8 per 100 PY; incidence rate ratio=3.61; p<0.001) and among patients in group B compared with group C (16.4 vs. 4.8 per 100 PY; incidence rate ratio=3.42; p=0.041). The effectiveness of ABP 501 after 12 weeks of treatment was assessed in patients naïve to ADA (group A + B; n=219): 188 patients (85.8%) had a clinical response, including 165 (75.3%) who achieved a steroid-free remission. Among the patients who responded at 12 weeks, a subsequent loss of response was reported in 17 subjects (9.0%). At the end of follow-up, 56 patients (10.0%) interrupted the treatment, with higher treatment persistency estimations for patients in group C compared with group A and B (log-rank p<0.001). Conclusion: This is the first prospective study on the use of ADA biosimilar ABP 501 in IBD. Safety and effectiveness of ABP 501 seem to be overall similar to those reported for ADA originator. Switching from originator to ABP 501 was safe and effective.